Understanding The Genesis Creation Accounts: Unity Or Duality? - Tauran, Edgar Willem Melko; Gosal, Fellix (Jurnal Ilmiah Wahana Pendidikan, 2025)
Scholars, theologians, and lay readers have long disagreed about the creation stories included in chapters 1 and 2 of Genesis. Some contend that these stories show a dichotomy of traditions, while others insist that they narrate a single story. To ascertain whether Genesis 1 and 2 are complementary or conflicting, this article evaluates their literary, linguistic, and theological aspects. Key Hebrew phrases, structural patterns, and thematic connections—such as the function of plants, the lack of rain, and humanity's obligation to cultivate the ground—are examined through careful textual analysis. Additionally, it affirms the text's wholeness and coherence from a Seventh-day Adventist perspective while analyzing historical-critical viewpoints, such as the Documentary Hypothesis. The findings suggest that rather than being at odds, the two narratives offer complementary interpretations of God's creative act, highlighting both the cosmic order of creation and humanity's special place within it. By providing a fair interpretation of these key texts, this work advances our understanding of the Genesis creation story and its theological ramifications